Differences in sprint ability, agility and vertical jump between professional and amateur soccer players in Bosnia and Herzegovina - Šunje, E.; Colakhodžic, E.; Novakovic, R.; Skoko, S. (Sportski Logos, 2021)
The aim of investigation was to determine the differences in linear speed (SPRINT30), agility (TT), and the explosive power of vertical jump (CMJ) between adult professional and amateur soccer players in Bosnia and Herzegovina. Forty-seven (47) soccer players were included in the research and were divided in two sample groups: professional soccer players of CSC Zrinjski Mostar who play at the elite level of competition - BiH Premier League (n = 22) and amateur soccer players of FC Velež Mostar who play at the second level of competition- First League of FBiH (n = 25).The study was conducted in February 2019, at the beginning of the second part of 2018/19 soccer season in BiH. The results of descriptive statistics show that professional soccer players are, on average, older (24.59 ± 4.15 vs 22.00 ± 2.95), taller (185.04 ± 6.33 vs 182.44 ± 6.99), and have a larger body mass (80.77 ± 6.92 vs 76.96 ± 8.64). The values of lower-limb explosive power, flight time CMJTIME (.63 ± .56s vs .65 ± .57s) and jump height CMJHIGH (40.95 ± 4.70cm vs 39.70 ± .4.15cm) show that, on average, professional soccer players have better results. The values of the ability to change the direction quickly (TT) are higher in professional soccer players (9.43 ± .33s vs 10.07 ± .43s), and it is the case with the linear speed tested by the test SPRINT30 (4.15 ± .12s vs 4.33 ± .15s). As for the variables defining lower-limb explosive power, the average values of CMJTIME and CMJHIGH are again slightly on the side of professionals as compared to amateurs (0.57 ± 0.03s vs 0.56 ± 0.03s) and (40.95 ± 4.70cm vs 39.70 ± 4.15 cm). T test for independent samples determined the differences in arithmetic mean between professional and amateur soccer players in Bosnia and Herzegovina in the treated variables. We noted here a statistically significant age difference between these two groups at the level of .95% (p =0.05) (sig. 0.017) and the difference between the variables defining the linear speed in SPRINT30 and TT agility at the level of .99% (p=0.01) (sig.0.000). In the variables defining lower-limb explosive power, the groups did not differ statistically in jump height and flight time. Based on the analysis of the results obtained, we may conclude that professional and amateur soccer players in BiH differ statistically significantly by age, linear speed and agility, and that there is no statistically significant difference in terms of lower-limb power/strength and the ability to jump vertically. We may conclude that professional teams rely more on more experienced players, while the second-level teams rely on young players who are eager to prove themselves, and that in training selection and technology, professional teams pay more attention to sprint speed and agility ability compared to amateur soccer players and second-level players. The soccer players do not differ statistically in their ability to jump vertically, so we can say that training technology, selection and programs in that domain are the same at both competition levels.